EXPLORING THE INFLUENCE OF LIFE INSURANCE DEMAND IN ADDIS ABABA, ETHIOPIA - Месфін Яйна Ганта; Кунджал Сінха (Фінансово-кредитна діяльність: проблеми теорії та практики)
The demand for life insurance plays a vital role in financial planning and risk management, particularly in developing countries like Ethiopia. This study investigates the factors influencing life insurance demand in Addis Ababa, Ethiopia. Using an explanatory research design and a quantitative methodology, data were gathered from 343 customers through questionnaires and applied in Statistical Packages of Social Science (SPSS) software version 27. Descriptive statistics, such as frequency and percentage distributions, were used to summarize the data, while multiple linear regression analysis identified key determinants of life insurance demand. The findings highlight education, income, public awareness, urbanization, and inflation as significant factors. Education emerged as the most critical, with individuals possessing higher levels of education more likely to recognize the importance of life insurance. Urbanization also contributes positively by enhancing life expectancy and improving access to insurance services. Income and public awareness further encourage life insurance adoption, while inflation hinders demand by reducing purchasing power. The study recommends targeted strategies to promote life insurance adoption. These include enhancing education, expanding insurance services in urban areas, designing products tailored to higher-income groups, and addressing inflation concerns with policies that incorporate inflation protection. Public awareness campaigns can also bridge knowledge gaps, particularly in urban areas, fostering informed decisions and improving financial security in Ethiopia. Growing demand and economic growth are driving a major transition in Addis Ababa's life insurance sector. A key factor in determining market dynamics is the quantity of insurance companies and the size of their financial assets. Insurance companies must adjust to the rising demand by fortifying their financial resources, boosting their investment plans, and enhancing service provision in order to preserve market stability and expansion. Policymakers, insurers, and other stakeholders must comprehend these economic and financial factors in order to promote a robust and prosperous insurance industry in Ethiopia.